A word order typology of adnominal person - Höhn Georg F.K. (Linguistic Typology)
This paper investigates cross-linguistic variation in the expression of adnominal person (persn; cf. English “we linguists”) based on a survey of 114 languages, focusing on word order. Two subtypes are distinguished according to whether persn is expressed by an independent pronoun as in English or by a morphologically dependent marker. Prenominal adnominal pronouns are the most common type of persn marking overall, while the morphologically dependent markers are predominantly postnominal (or phrase-final). The order of persn marking relative to its accompanying noun is shown to interact with head-directionality (VO/OV-order, position of dependent genitives, adpositions) and with the position of demonstrative modifiers (prenominal/postnominal) using generalised linear mixed-effects models. Theoretical implications and possible explanations for deviations are discussed concerning variation in the encoding of persn as head or phrasal modifier and its (lack of) co-categoriality with demonstratives.